Perioperative Factors Associated with HCAHPS Responses of 2, 758 Surgical Patients. Issue 4 (28th December 2014) - Maher, Dermot P.; Wong, Waylan; Woo, Pauline; Padilla, Cesar; Zhang, Xiao; Shamloo, Bahman; Rosner, Howard; Wender, Ronald; Yumul, Roya; Louy, Charles
Abstract Objective To determine perioperative treatments and events associated with Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey responses. Design Retrospective analysis. Setting Single tertiary care, academic, urban, level‐1 trauma center. Participants Final cohort represents 2, 758 consecutive surgical inpatients meeting criteria for evaluation by HCAHPS. Exposures Responses to four HCAHPS questions were compared against 19 perioperative treatments and events. Measures Positive and negative responses to HCAHPS questions. Results Patients responding affirmatively with a "9" or "10" to "what number would you use to rate this hospital" were associated with decreased lengths of hospitalization, greater lengths of surgery, decreased intraoperative opioid equianalgesic doses, greater preoperative midazolam doses, shorter post anesthesia care unit (PACU) lengths of stay and decreased last PACU numerical rating scale (NRS) pain scores. Patients responding affirmatively with "yes, definitely" to "would you recommend this hospital to your family" were associated with decreased last PACU NRS pain scores. Patients responding affirmatively with "yes, always" to "How often did the hospital staff do everything to help with your pain" were associated with decreased hospital lengths of stay, decreased chronic benzodiazepine use, greater chronic NSAID use, and decreased PACU lengths of stay. Patients responding affirmatively with "yes, always" to "how often was your pain well controlled" were associated with decreased chronic opioid use, decreased chronic benzodiazepine use, greater chronic NSAID use, increased length of surgery, decreased last PACU NRS pain score, and decreased first PACU NRS pain scores. Subgroup analysis of patients undergoing different types of surgery further characterized factors associated with HCAHPS responses among different surgical populations. Conclusions These data suggest that demographic factors, preadmission medications, and PACU pain scores but not analgesic medications are associated with patient satisfaction with regards to both pain management and overall satisfaction.